2011
DOI: 10.1016/j.febslet.2011.12.029
|View full text |Cite
|
Sign up to set email alerts
|

FLU, a negative feedback regulator of tetrapyrrole biosynthesis, is physically linked to the final steps of the Mg++‐branch of this pathway

Abstract: Edited by Ulf-Ingo FlüggeKeywords: Protochlorophyllide FLU Glutamyl-tRNA reductase Arabidopsis a b s t r a c t Regulation of tetrapyrrole biosynthesis in higher plants has been attributed to negative feedback control. Two effectors of feedback inhibition have been identified, heme and the FLU protein. Inhibition by heme implicates the Fe-branch via regulation of the initial step of tetrapyrrole synthesis. In the present work a FLU-containing chloroplast membrane complex was identified, that besides FLU compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 27 publications
3
96
0
Order By: Relevance
“…Moreover, a POR-GluTR interaction was found by the same approach. This interaction is consistent with the findings reported by Kauss et al (2012), who proposed the formation of a protein complex consisting of CHL27, POR, FLU, and GluTR in chloroplasts of dark-grown plants. The POR reaction provides Chlide, one of the two substrates of CHLG.…”
Section: Lil3-mediated Protein-protein Interactionssupporting
confidence: 93%
“…Moreover, a POR-GluTR interaction was found by the same approach. This interaction is consistent with the findings reported by Kauss et al (2012), who proposed the formation of a protein complex consisting of CHL27, POR, FLU, and GluTR in chloroplasts of dark-grown plants. The POR reaction provides Chlide, one of the two substrates of CHLG.…”
Section: Lil3-mediated Protein-protein Interactionssupporting
confidence: 93%
“…Either CHLH activity contributes to the methyltransferase activity, as proposed by Shepherd et al (2005), or CHLH is needed for the stability of a multienzymatic complex including CHLM. In this context, a protein complex consisting of CHL27, POR, GluTR, and other proteins has been recently reported for the tight repression of ALA synthesis in darkness by the negative regulator FLU in angiosperms (Meskauskiene et al, 2001;Kauss et al, 2012). It remains open whether other proteins of Chl synthesis, including the CHLH subunit and CHLM, are part of this protein complex.…”
Section: Chlm Activity Is Redox Dependent and Can Be Stimulated By Ntrcmentioning
confidence: 99%
“…Two important posttranslational regulators, FLU and Genome Uncoupled4 (GUN4), have been identified that modulate the enzyme activities of glutamyl-tRNA reductase (GluTR) and Mg chelatase, respectively. In response to accumulating PChlide, the FLU protein represses ALA synthesis in darkness by interaction with GluTR1 (Meskauskiene et al, 2001;Richter et al, 2010;Kauss et al, 2012), which is one of the two analyzed isoforms. GUN4 has been identified in a mutant screen for modifications of retrograde signaling between chloroplasts and the nucleus (Larkin et al, 2003).…”
mentioning
confidence: 99%
“…S3C). In dark, the flow of intermediates is rapidly attenuated by the FLU-protochlorophyllide-dependent repression of GluTR activity (Meskauskiene et al, 2001;Meskauskiene and Apel, 2002;Lee et al, 2003;Richter et al, 2010;Kauss et al, 2012). By inhibition of ALA synthesis, the rate-limiting step of TBS, the steady-state levels of MgP and MgPMME, were below the detection limit and protochlorophyllide is the only porphyrin, which accumulates in dark due to the light dependency of protochlorophyllide oxidoreductase (POR).…”
Section: Factors Influencing Gun4 Phosphorylationmentioning
confidence: 99%